2020
DOI: 10.26637/mjm0804/0063
|View full text |Cite
|
Sign up to set email alerts
|

Learning effect on an optimal policy for mathematical inventory model for decaying items under preservation technology with the environment of COVID-19 pandemic

Abstract: Due to the environment of corona virus pandemic, a huge problem arises in the market, due to which the retailer keeps his items lying, and those items start to deteriorate. He is unable to get the new goods from suppliers and get a shortage. We established an optimal policy for mathematical inventory model for decaying items under preservation technology (PT) with learning effect. This model is starting with partially backlogging shortage. The investment in Preservation technology is used so that the items dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Chang et al [6] explored a production-inventory model with a multi-stage supply chain that uses preservation technology to prevent deterioration and boost investment. In the context of preservation technology investment, Kumar et al [21] determined the optimal policies for deteriorating artifacts. Saha et al [32] identified the optimum dynamic marketing investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chang et al [6] explored a production-inventory model with a multi-stage supply chain that uses preservation technology to prevent deterioration and boost investment. In the context of preservation technology investment, Kumar et al [21] determined the optimal policies for deteriorating artifacts. Saha et al [32] identified the optimum dynamic marketing investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The consumer demand for the final product showed a linear dependency on the selling price and quality, and the manufacturing procedure was based on the theme of learning. Kumar et al [45] developed a learning effect model for a green environment. Considering a two-level dual-channel supply chain, Batarfi et al [46] examined the impact of learning and forgetting on manufacturing processes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reduced deterioration rate per unit product is λ(β) (0 < λ(β) < 1), where λ(β) = λ 0 e −ψβ . Here, λ 0 is the deterioration rate without investment in PT, β denotes the PT investment and ψ (ψ > 0) is the sensitive parameter of investment (motivated by Kumar et al [25] and Mashud et al [28]). This PT investment function is compatible with various industries.…”
mentioning
confidence: 99%